2008
DOI: 10.1080/15504260802313816
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine, Olanzapine, or Typical Antipsychotics for Alcohol Use Disorder in Patients With Schizophrenia

Abstract: Objectives: Previous research regarding the impact of olanzapine on substance use in patients with schizophrenia is mixed, and no data address its impact on alcohol use disorders. This retrospective study compared the effect of olanzapine to the effect of clozapine, an agent associated Mary F. Brunette, Christopher O'Keefe, and Alan I. Green are affiliated with the Department of Psychiatry, Dartmouth Medical School, White River Junction, VA. Brunette et al. 345 with improvements in alcohol use disorders i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Four observational studies (Brunette et al, 2006, 2008; Drake et al, 2000; Green et al, 2003) with available raw data reported the proportion of individuals with concurrent SSD and SUDs (predominantly alcohol) who remained abstinent (defined as either complete cessation of use or use without impairment) on clozapine versus other antipsychotics for the duration of follow-up. Characteristics of these studies are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Four observational studies (Brunette et al, 2006, 2008; Drake et al, 2000; Green et al, 2003) with available raw data reported the proportion of individuals with concurrent SSD and SUDs (predominantly alcohol) who remained abstinent (defined as either complete cessation of use or use without impairment) on clozapine versus other antipsychotics for the duration of follow-up. Characteristics of these studies are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…An important related issue concerns the effects of antipsychotic medication on substance use in this population. Most antipsychotics do not lessen substance use in patients with schizophrenia, with one exception – clozapine has been shown in many (albeit still preliminary) studies to do so across a variety of substances (e.g., alcohol, cannabis, tobacco) (Brunette et al, 2011; Brunette et al, 2006; Brunette et al, 2008; Buckley et al, 1999; Drake et al, 2000; George et al, 1995; Lee et al, 1998; Wu et al, 2013; Zimmet et al, 2000). Related to this, Mesholam-Gately et al, (2014) have observed, in a population of substance using patients with schizophrenia that in comparison with other antipsychotics, clozapine strengthens the hedonic experience associated with olfactory stimuli.…”
Section: Which Comes First? Epidemiology Of Substance Use and Schizopmentioning
confidence: 99%
“…Unfortunately, available data are somewhat mixed and not overly promising (Green, Noordsy, Brunette, & O’Keefe, 2008) for risperidone (Green, Burgess, Dawson, Zimmet, & Strous, 2003; Smelson et al, 2002; Smelson et al, 2004), olanzapine (Akerele & Levin, 2007; M.F. Brunette et al, 2008; Noordsy et al, 2001; Petrakis, Leslie, Finney, & Rosenheck, 2006; Smelson et al, 2006), quetiapine (E.…”
mentioning
confidence: 99%